Persulfurated Benzene‐Cored Asterisks with π‐Extended ThioNaphthyl Arms: Synthesis, Structural, Photophysical and Covalent Dynamic Properties. Issue 46 (27th June 2022) - Gahlot, Sapna; Gradone, Alessandro; Roy, Myriam; Giorgi, Michel; Conti, Simone; Ceroni, Paola; Villa, Marco; Gingras, Marc
Abstract: The synthesis of regioisomeric asterisks (5 ) and (6 ) incorporating a benzene core with six 1‐naphthylthio or six 2‐naphthylthio arms are reported in search for new materials with optoelectronic properties. The consequences on the extension of a π system surrounding a persulfurated benzene core provide a new avenue to study the structural, photophysical, and chemical properties of such family of all‐organic phosphors. It also diverts the persulfuration mechanism after two radical cyclizations for making a [5]dithiohelicene by‐product (7 ) and favors dynamic sulfur component exchange reactions surrounding the core. These exchanges convert asterisks (5 ) and (6 ), non‐phosphorescent at 20 °C to the highly phosphorescent (4 ) ( ϕ ∼100 %, solid state at 20 °C). For asterisks (5 ) and (6 ), the absence of the typical phosphorescence of the per(phenylthio)benzene core in the solid state at 20 °C and the presence of a weak naphthalene‐based phosphorescence at 77 K is attributed to an energy transfer from the triplet state of the persulfurated benzene core to the outer naphthalene moieties, resulting in an antenna system. Abstract : Regioisomeric asterisks (5‐6 ) with naphthylthio arms are reported. Consequences on π‐extension around a persulfurated benzene bring different structural, photophysical and chemical properties. Sulfur exchanges reactions convert non emissive (5 –6 ) into the best one (4 ). π‐Extension inhibits luminescence of a hexakis(phenylthio)benzene unit. Sc‐XRD shows structural distortions and different behaviors of (5 –6 ).